PENDAMPINGAN PETANI SAYURAN MELALUI PENGENDALIAN RAMAH LINGKUNGAN OPT PARE PADA KELOMPOK TANI MUTIARA PATTIMURA - Masauna, Esther Dolfina; Sahetapy, Betty; Uruilal, Costanza; Rumahlewang, Wilhelmina (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2023)
Farmers in the Mutiara Pattimura Farmers group are vegetable and fruit farmers from Taeno village who help with work. So far, the farmers in this farmer group have been intensively cultivating vegetable and fruit crops, including bitter gourd, long beans, kale, Chinese pumpkin, beligo (gourd), chili and basil. Bitter gourd pests need serious attention before and after planting until harvest, so assistance is needed in the form of direct surveys to farmers' fields. Preventive management of vegetable pests, especially bitter gourd through good and correct cultivation techniques, can be carried out before and after planting to manage the presence of pests in the area. The problem with PKM activities is what pests are found in the bitter melon planting area, how is the cultivation system carried out by farmers in relation to the management of bitter melon pests. Good and correct cultivation techniques before and after planting, the presence of OPT can be managed properly so that it can increase bitter melon production. Based on the problems, the following solutions are offered: Knowledge related to bitter melon cultivation techniques, Knowledge of environmentally friendly OPT control in relation to cultivation techniques. PKM activities are still deemed necessary to be carried out continuously to obtain and convey information and direct discussions with farmers so that they can provide benefits for farmers related to knowledge about pests and appropriate control measures so that optimal production can be achieved.